The potential roles of Pinto bean (Phaseolus vulgaris cv. Pinto) bioactive peptides in regulating physiological functions: Protease activating, lipase inhibiting and bile acid binding activities. (June 2017) - Ngoh, Ying-Yuan; Choi, Sy Bing; Gan, Chee-Yuen
Highlights: PBPs activated protease activity via binding to Asp52, Tyr113 and Tyr114 of pepsin. PBPs inhibited lipase activity via blocking Ser153 and His264 of lipase. PBPs bound to C5-OH, C11-OH, C15-OH or C21-OH of bile acids. PBP3 was the most potent protease activator (64.00%) and bile acids binder (70.54%) PBP5 was the most potent lipase inhibitor (86.67%) Abstract: The aim of the study was to explore the physiological effects of Pinto bean peptides (PBP) and their structure-activity relationships. Five pre-screened PBPs were investigated. The results showed that PBPs enhanced the protease activity ranging from 333 to 400%, and conversely, they inhibited lipase activity ranging from ∼23 to ∼87%. It was suggested that the binding of PBP to pepsin (i.e. Asp52, Tyr113 and Tyr114) resulted in a broad flap extension and enlarged the S3 pocket, which made the active site more accessible, whereas, catalytic residues (i.e. Ser153 and His264) of lipase were found strongly bound to PBPs and preventing the enzyme from hydrolysing lipids. PBPs also shown their ability in binding bile acid ranging from ∼18 to ∼71% via hydrogen bonds to the C5-OH, C11-OH, C15-OH or C21-OH of cholic acid and deoxycholic acid. This study highlighted the effectiveness and mechanism of PBP in preventing obesity, hyperlipidaemia and hypercholesterolemia.